2016
DOI: 10.1111/cdev.12567
|View full text |Cite
|
Sign up to set email alerts
|

Controlling and Autonomy‐Supportive Parenting in the United States and China: Beyond Children's Reports

Abstract: Research comparing the predictive power of parents' control and autonomy support in the United States and China has relied almost exclusively on children's reports. Such reports may lead to inaccurate conclusions if they do not reflect parents' practices to the same extent in the two countries. A total of 394 American and Chinese children (M = 13.19 years) and their mothers reported on mothers' controlling and autonomy-supportive parenting in the academic arena; trained observers coded such parenting in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 99 publications
9
102
0
3
Order By: Relevance
“…Furthermore, emotion dysregulation is an internal process, which is likely to be predicted more strongly by adolescents' perceptions of conflict than by parents' reports. In support of this argument, a recent study found that, although parents' and adolescents' reports are equally good predictors of overt aspects of adjustment, only children's reports predicted children's emotional functioning (Cheung et al, 2016). A potential downside of using only adolescent-reported data is that effects might be inflated, due to common method variance.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Furthermore, emotion dysregulation is an internal process, which is likely to be predicted more strongly by adolescents' perceptions of conflict than by parents' reports. In support of this argument, a recent study found that, although parents' and adolescents' reports are equally good predictors of overt aspects of adjustment, only children's reports predicted children's emotional functioning (Cheung et al, 2016). A potential downside of using only adolescent-reported data is that effects might be inflated, due to common method variance.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Additionally, parents do not always reflect consciously about their parenting behaviors and some parenting behaviors happen routinely or spontaneously, and are therefore difficult to report [Gardner, 2000]. The association between mothers' reported and observed parenting behaviors is found to be weak [Cheung, Pomerantz, Wang, & Qu, 2016].…”
Section: Introductionmentioning
confidence: 96%
“…A estrutura tridimensional obtida carateriza-se por um fator de autonomia psicológica (seis itens), um fator de clima positivo (quatro itens) e um fator de conhecimento (cinco itens). Estes fatores são consistentes com a literatura sobre EEP (e.g., Bean & Northrup, 2009;Cheung et al, 2016;Morris et al, 2013). O fator de autonomia psicológica refere-se à promoção da autonomia do adolescente através das ações que promovem o pensamento independente e a tomada de decisão informada e consciente.…”
Section: Discussionunclassified
“…A investigação sobre EEP tem recorrido, mais comummente, a questionários e a entrevistas a pais e a filhos (Hoff, Laursen, & Tardif, 2002;Simons & Conger, 2007). Os relatos de pais e filhos tendem a ser diferentes (Hoff et al, 2002) ou a apresentar correlações de valor baixo a moderado (Cheung, Pomerantz, Wang, & Qu, 2016). Contudo, a literatura tem demonstrado que as perceções dos filhos sobre os EEP, nomeadamente dos adolescentes, são uma medida mais fidedigna do que a perceção dos pais, na medida em que estão menos sujeitas a enviesamento inerente à desejabilidade social (Morsbach & Prinz, 2006), e também porque têm sido apontadas como melhores preditores do desenvolvimento e/ou adaptação dos adolescentes (Cheung et al, 2016;Pelegrina, Garcia Linares, & Casanova, 2003).…”
Section: Perceção Dos Adolescentes Sobre Os Estilos Educativos Parentaisunclassified
See 1 more Smart Citation